Protective role of fish oil (Maxepa) on early events of rat mammary carcinogenesis by modulation of DNA-protein crosslinks, cell proliferation and p53 expression - Manna, Sangita (BioMed Central, 2007)
BACKGROUND: Fish oil is known to protect from many types of cancers of the colon, liver, breast, prostate and lung [1-3]. The objective of the present study was to evaluate the role of fish oil [Maxepa, supplemented at a dose of 0.5 ml is equivalent to 90 mg eicosapentaenoic acid (EPA) and 60 mg docosahexaenoic acid (DHA)] on cell proliferation, expression of p53 tumor suppressor protein and DNA protein crosslinks (DPCs) in a defined model of chemical rat mammary carcinogenesis. Mammary carcinogenesis was initiated by a single, intravenous (i.v.) tail vein injection of 7,12 dimethylbenz(α)anthracene (DMBA) at a dose of 5 mg DMBA/2 ml corn oil/kg body weight in female Sprague-Dawley rats at 7 weeks of age. Fish oil supplementation was started daily, 2 weeks prior to DMBA injection and continued for 24 (31 weeks of animal age) weeks and 35 (42 weeks of animal age) weeks of post DMBA injection, for histopathological and immunohistochemical and for morphological studies, respectively. RESULTS: Our results indicate the chemopreventive effect of fish oil (Maxepa) on DMBA-induced rat mammary carcinogenesis. Administration of fish oil further showed a prominent reduction of cell proliferation (24.34%, P = 0.001); DPCs (25%, P < 0.001) and an increased expression of p53 protein (4.636 ± 0.19, P < 0.001) in preneoplastic mammary tissue when compared to carcinogen control counterpart. Histopathological and morphological analyses were carried out as end-point biomarkers. CONCLUSION: Our study thus provides evidence for the anticarcinogenic effect of fish oil (Maxepa) in limiting mammary preneoplasia in Sprague-Dawley rats.